Drought resistance of wild, cultivars and introgressive forms of winter wheat (Experimental biology, 2016)
Results of field and laboratory researches on screening wild, cultuvars and  introgressive forms of winter wheat on drought resistance are given in this paper.Introgressive forms obtained by interspecific hybridization of varieties of winter wheat (Triticum aestivum L.) of Kazakh selection with wild species Triticum timopheevii, Triticum militinae, Aegilops cylindrical, Aegilops triaristata. There are tested some morpho - physiological, physiology - biochemical, breeding and genetic indexes as  a criteria of drought resistance. It is established that on accumulation of vegetative biomass in different growth phases were in the lead Eritrospermum 350 x T.kiharae, Progress x T.timopheevii. On biomass accumulation  in different growth phases were in the lead Eritrospermum 350 x T.kiharae, Progress x T.timopheevii. Genotypes are determined by the content of free proline in seedlings  for the breeding  progresson  to drought tolerance: Eritrospermum 350 x T.kiharae, (Bezostaya1 x T.militinae) x T.militinae (introgressive forms); T.kiharae, Ae.cylinrica (wild ); Eritrospermum 350, Steklovidnaya 24 (wheat varieties). The structure of root system for wild is defined; cultivars and the introgressive forms, perspective samples at various stages of development of sprouts are revealed. Drought resistance sources against of crop productivity are allocated. The most legible results of correlation to drought resistance on an index "the mass of 1000 grains", defined 6 introgressive forms exceeding a grade are established.
Keywords: wheat; introgressive forms; wild species; drought resistance; vegetative biomass; root system; chlorophyll; proline; crop productivity.